Non‐targeted analyses of organic compounds in urban wastewater. (29th October 2014) - Alves Filho, Elenilson G.; Sartori, Luci; Silva, Lorena M. A.; Silva, Bianca F.; Fadini, Pedro S.; Soong, Ronald; Simpson, Andre; Ferreira, Antonio G.; Simpson, Andre J.
<x xml:space="preserve">Abstract</x> A large number of organic pollutants that cause damage to the ecosystem and threaten human health are transported to wastewater treatment plants (WWTPs). The problems regarding water pollution in Latin America have been well documented, and there is no evidence of substantive efforts to change the situation. In the present work, two methods to study wastewater samples are employed: non‐targeted 1D (13C and 1H) and 2D NMR spectroscopic analysis to characterize the largest possible number of compounds from urban wastewater and analysis by HPLC‐(UV/MS)‐SPE‐ASS‐NMR to detect non‐specific recalcitrant organic compounds in treated wastewater without the use of common standards. The set of data is composed of several compounds with the concentration ranging considerably with treatment and seasonality. An anomalous discharge, the influence of stormwater on the wastewater composition and the presence of recalcitrant compounds (linear alkylbenzene sulfonate surfactant homologs) in the effluent were further identified. The seasonal variations and abnormality in the composition of organic compounds in sewage indicated that the procedure that was employed can be useful in the identification of the pollution source and to enhance the effectiveness of WWTPs in designing preventive action to protect the equipment and preserve the environment. Copyright © 2014 John Wiley & Sons, Ltd.